Impact of procedures during prosthodontic treatment on patients' perceived burdens. Issue 1 (January 2015) - Hacker, Tim; Heydecke, Guido; Reissmann, Daniel R.
Abstract Objectives To assess patient-perceived process-related quality of care in patients undergoing different prosthodontic treatments, and to investigate whether perceived burdens are related to specific procedures during prosthodontic treatments, i.e., to specific treatment components. Methods In this non-randomised prospective intervention study, 104 dental patients (mean age: 52.2 ± 13.9 years, 50% female) were included. Burdens during treatments with fixed dental prostheses (FDP, n = 90), removable dental prostheses (RDP, n = 10), and complete dentures (CD; n = 4) were assessed with the Burdens in Prosthetic Dentistry Questionnaire (BiPD-Q). The BiPD-Q total score was calculated as mean of all 25 items, and subscale scores were derived from items corresponding to six specific treatment components (anesthesia, preparation, impression, provisional care/try-in, fixation, global perception), with values ranging from 0 (best) to 100 (worst). Subscale scores were compared by using repeated-measures ANOVA, paired t-tests, and effect sizes, to identify treatment components with highest burdens. Results Mean BiPD-Q total score was 22.1, ranging from 8.6 for patients with CD to 24.0 for FDP patients. Perceived burdens differed significantly between treatment components, with highest burdens for anesthesia (score: 34.0), followed by preparation (score: 26.8) and impression (score: 24.7). When subscale score for anesthesia was compared to scores for other treatment components, effect sizes were medium to large. Conclusion While prosthodontic treatment is overall perceived as only moderately burdening, specific treatment components differ significantly in perceived burdens. Clinical significance Anesthesia, preparation, and impression are treatment components with most unpleasant perceptions, offering the highest potential for improvements for patient-perceived process-related quality of care in prosthetic dentistry.